Prevalence of Oral Candidasis in Oral Cancer Expansion - Sharma, Dr. Nishant; Shrivastav, Dr. Archana (International Journal of Innovative Research in Medical Science, 2017)
Oral cancer is a multifactorial disease and beside with many potentially malignant disorders, chronic oral Candidiasis is rarely but can transfer into oral cancer. Oral Candidiasis includes the exterior of whitish, velvety plaques on the mucous membranes of the mouth and tongue. Candida as a pathogen can cause both outward and grave systemic disease. The finding of its deep seated infections remains a great challenge. Identification and characterization of antigens would be useful in the diagnosis and treatment of Candida infections. Present study was aimed to culture and identify C. albicans from patients with suspected oral cancer and separate proteins put in on SDS-PAGE to identify its patterns. The prominently were resolved single polypeptide band of approximately 46 KDa.